Influência do sistema histaminérgico cerebelar na aprendizagem motora e memória emocional de camundongos - Silva-Marques, Bruna (2020)
The neural histaminergic system innervates the cerebellum, with high density of fibers in the vermis and flocculus. Experimental evidence indicates that cerebellum is involved in various non-motor as well as motor operations. However, the role of histaminergic system in these functions is not clear. In this present study, we investigated the effects of intracerebellar histamine injections and H1, H2and H3 receptor antagonist injections (chlorpheniramine, ranitidine and thioperamide, respectively) on motor performance motor learning, balance and anxiety in mice. For this, we used Swiss albino mice weighing 25-35g and maintained in a thermoregulated environment. The cerebellar vermis of male mice was implanted with guide cannula. After three days of recovery, the animals received microinjections of saline, histamine, chlorpheniramine ranitidine or thioperamide in different concentrations. Five minutes postinjection, the rota-rod and balance beam test was performed in three stages. After evaluation of motor performance and balance, animals were submitted to elevated plus maze. Statistical analysis included the homogeneity test and multi-factor analysis of variance (ANOVA) followed by Duncan’s Multiple Range test and Pearson test for correlation between motor and non-motor functions. A p value of ≤0.05 was required for significance. The results showed a possible facilitation of histamine at the highest dose in the evaluation of learning and motor performance in the rota-rod. In addition, the results showed an impairment when tested at the 0.052 dose of CPA, at the lowest doses of ranitidine and also at highest dose of thioperamide. We do not found any correlation between motor skills and anxiety in this study. Together, the results suggest that cerebellar histaminergic projections are involved in motor learning and make a modulating role in the cerebellar circuit to ensure that movements are performed efficiently. Futhermore, the manipulation of the histaminergic system can influence other systems.